2017
DOI: 10.1111/jocn.13806
|View full text |Cite
|
Sign up to set email alerts
|

Improving support and education of low‐income baby boomers diagnosed with chronic hepatitis C virus infection through universal screening

Abstract: Aims and objectives The objective of this study was to identify support needs of low income baby boomers recently diagnosed with chronic hepatitis C virus infection. Background The United States Preventive Services Task Force has endorsed one-time screening of all baby boomers (born 1945 to 1965) for hepatitis C because 75% of the estimated 2 to 3 million persons with chronic infection are in this age range. We hypothesized that persons diagnosed by routine screening would have significant psycho-emotional, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Prior literature suggests that more modest designs that emphasize EHR‐based tools can also achieve remarkable increases in screening and linkage to care 12‐ . However, additional evidence‐based interventions such as reflex RNA testing among patients with positive antibody results, patient navigation 15 and case management 16 may further enhance HCV screening and linkage to care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior literature suggests that more modest designs that emphasize EHR‐based tools can also achieve remarkable increases in screening and linkage to care 12‐ . However, additional evidence‐based interventions such as reflex RNA testing among patients with positive antibody results, patient navigation 15 and case management 16 may further enhance HCV screening and linkage to care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients need greater assurance that currently available treatments have dramatically increased the likelihood of being cured. Additional support for emotional and social challenges need to be provided such as assisting low‐income older adults with more comorbidities and/or barriers in access to care 16 . Similarly, continued knowledge gaps among patients, particularly those earlier in the screening process, highlight an opportunity for better patient education when interfacing with primary care providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No study compared harms systematically using comparison groups associated with different screening approaches. Harms informed by the alladult review included physical harms of screening (two studies) (48,49); anxiety/stress related to testing or waiting for results (five studies) (49-53); cost (one study) (54); anxiety related to receiving positive results (one study) (55); interpersonal outcomes (e.g., problems related to family, friends from learning HCV infection status) (five studies) (51,(55)(56)(57)(58); attitudes toward persons with hepatitis C, including stigma (11 studies) (49,55,(57)(58)(59)(60)(61)(62)(63)(64)(65); time for screening (two studies) (49,66); and false-positive results, including among left ventricular assist device patients, possibly precluding heart transplantation (six studies) (67)(68)(69)(70)(71)(72). Harms informed by the pregnancy review included physical harms of screening (one study) (73), anxiety (five studies) (74)(75)(76)(77)(78), stigma (one study) (77), psychological issues (two studies) (73,79), fears related to sexual relationships (one study) (80), legal ramifications and potential loss of infant custody (one study) (81), decreased quality of life (one study) (82), social repercussions (one study)…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…50 Studies have identified psycho-emotional and social challenges that reflect poor knowledge and barriers to supportive care of patients who have been newly diagnosed with chronic HCV. 51 Thus, patients with chronic HCV need to be offered educational resources that can be efficiently provided on a mobile app to address these issues. 21,52 Barrier #2: Linkage to HCV Care.…”
Section: Barriers In the Quest To Eliminate Hcvmentioning
confidence: 99%